Sex, drugs, and bitcoin:How much illegal activity Is financed through cryptocurrencies? - Foley, Sean (The review of financial studies, 2019)
© The Author(s) 2019. Cryptocurrencies are among the largest unregulated markets in the world. We find that approximately one-quarter of bitcoin users are involved in illegal activity.We estimate that around 76 billion of illegal activity per year involve bitcoin (46% of bitcoin transactions), which is close to the scale of the U.S. and European markets for illegal drugs. The illegal share of bitcoin activity declines with mainstream interest in bitcoin and with the emergence of more opaque cryptocurrencies. The techniques developed in this paper have applications in cryptocurrency surveillance. Our findings suggest that cryptocurrencies are transforming the black markets by enabling black e-commerce. (JEL G18, O31, O32, O33)